+0  
 
0
48
1
avatar

Let $r$ and $s$ be the roots of $x^2 - 6x + 2 = 0.$ Find $(r - s)^2.$

 Jan 24, 2021
 #1
avatar+116126 
+1

The  sum of the roots =  6                      The product of the roots   = 2

So                                                              So 

r+ s  =  6                                                     rs   = 2 

 Square both sides                                    2rs  =  4

r^2  + 2rs  + s^2   =  36                              -2rs  =  -4

r^2 + s^2  = 36 - 2rs                                  -4rs  = -8

 

(r - s)^2   = 

 

r^2   -  2rs   +  s^2  =    

 

[ r^2  +  s^2 ]    -  2rs   =

 

[36 -2rs]  - 2rs  =

 

36  -  4rs   =

 

36  - (-8)  =

 

44

 

 

cool cool cool

 Jan 24, 2021

50 Online Users

avatar
avatar
avatar
avatar